Sociocultural valuation of ecosystem services in Southern Patagonia, Argentina. - Peri, Pablo Luis (2021)
Understanding sociocultural values towards ecosystem services (ES) facilitates a decision-making process across multiple management objectives. The aim of this chapter was to analyse the stakeholders’ perceptions of ES, wellbeing and connectedness to nature at regional level in Southern Patagonia (Santa Cruz Province, Argentina). For this, we designed a questionnaire and conducted 451 face-to-face semi-structured interviews, in which 168 corresponded to local residents and 283 to foreign visitors. Ecosystem services were classified depending on the degree of perceived importance and vulnerability for wellbeing. From this, 12 ES (5 provisioning, 6 cultural and 1 regulating) were perceived as important for wellbeing. Analysing the perceptions of vulnerable ES by each local stakeholder, we found that both groups of locals and decision-makers perceived provisioning services (mainly livestock, fresh water, timber, fishing and shellfish) and regulating (erosion control, habitat for species and climate regulation) as important ones. Survey respondents generally indicated a high level of connectivity with nature being similar for both locals and visitors. Our results showed that social perception of values can substantially contribute to identify ES by focusing on the conflicts that emerge among different stakeholder groups. The sociocultural information of the present study can provide important inputs into negotiations in a decision-making process, allowing participants to compare positive and negative impacts of various options for ES management.